Mucin-Type O-Glycosylation Proximal to β-Secretase Cleavage Site Affects APP Processing and Aggregation Fate - Singh, YashoNandini; Regmi, Deepika; Ormaza, David; Ayyalasomayajula, Ramya; Vela, Nancy; Mundim, Gustavo; Du, Deguo; Minond, Dmitriy; Cudic, Maré (Frontiers in Chemistry, 2022)
The amyloid-β precursor protein (APP) undergoes proteolysis by β- and γ-secretases to form amyloid-β peptides (Aβ), which is a hallmark of Alzheimer’s disease (AD). Recent findings suggest a possible role of O-glycosylation on APP’s proteolytic processing and subsequent fate for AD-related pathology. We have previously reported that Tyr681-O-glycosylation and the Swedish mutation accelerate cleavage of APP model glycopeptides by β-secretase (amyloidogenic pathway) more than α-secretase (non-amyloidogenic pathway). Therefore, to further our studies, we have synthesized additional native and Swedish-mutated (glyco)peptides with O-GalNAc moiety on Thr663 and/or Ser667 to explore the role of glycosylation on conformation, secretase activity, and aggregation kinetics of Aβ40. Our results show that conformation is strongly dependent on external conditions such as buffer ions and solvent polarity as well as internal modifications of (glyco)peptides such as length, O-glycosylation, and Swedish mutation. Furthermore, the level of β-secretase activity significantly increases for the glycopeptides containing the Swedish mutation compared to their nonglycosylated and native counterparts. Lastly, the glycopeptides impact the kinetics of Aβ40 aggregation by significantly increasing the lag phase and delaying aggregation onset, however, this effect is less pronounced for its Swedish-mutated counterparts. In conclusion, our results confirm that the Swedish mutation and/or O-glycosylation can render APP model glycopeptides more susceptible to cleavage by β-secretase. In addition, this study sheds new light on the possible role of glycosylation and/or glycan density on the rate of Aβ40 aggregation.